UTILIZATION OF DURIAN SKIN BRICKETS AS AN ENVIRONMENTALLY FRIENDLY TECHNOLOGY ALTERNATIVE - Sari, Ega Dwi Permata; Setiawan, Iwan; ardana, Rendy Wikrama W; Nursaadah, Euis; Karyadi, Bhakti (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2024)
The research objective focuses on testing the quality of Durian Skin Briquettes as an alternative environmentally friendly technology. The type of research is experimentation and development with models (R&D) . Data collection techniques are experimentation, documentation and literature study. The data analysis method in this research involves the application of quantitative and qualitative approaches. Durian skin briquettes are divided into 2 groups: A1 (90% yellow durian skin charcoal: 10% adhesive), A2 (90% green durian skin charcoal: 10% adhesive). Durian skin briquette test results comparing 90% green durian skin charcoal with 10% adhesive showed the best results with a total heat of 4748 k cal/kg. The conclusion of this research is that the resulting calorific value efficiency is 4748 k cal/kg in green durian skin briquettes.